Wydobyte z cienia O nowym projekcie: Adam Mickiewicz. Proza artystyczna: opowiadania, szkice, fragmenty. Prose artistique: contess, essais, fragments, wstęp i oprac. Joanna Pietrzak-Thébault, Wydawnictwo Instytutu Badań Literackich, Warszawa 2013. - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2013)
Brought out of the shadow The article discusses Adam Mickiewicz.Proza artystyczna: opowiadania, szkice, fragmenty. Prose artistique: contess, essais, fragments, which is a bilingual (French-Polish) endeavour in translation and editing – broadly speaking, one of historical and literary character. The book was edited by Joanna Pietrzak-Thébault in collaboration with whom Maria Prussak, Krzysztof Rutkowski and Jacek Wójcicki. Maria Prusak initiated the project and coordinated the proceedings of the team. Mickiewicz’s works in French received new translation and were edited anew.